Unlocking Africa’s Green Hydrogen Economy - Kithinji, Brian; Echessa, Bolly; Bakari, Elijah (HAPSc Policy Briefs Series, 2025)
Green hydrogen, derived from renewable energy sources through electrolysis, presents a pivotal opportunity in the global shift towards sustainable energy systems. As nations accelerate their decarbonization efforts to combat climate change, the role of green hydrogen has become increasingly crucial. It offers a versatile energy carrier capable of decarbonizing sectors that are challenging to electrify directly, such as the transportation, aviation, and the chemicals industry. However, several barriers hinder its widespread adoption in Africa, including high production costs, inadequate policy frameworks, infrastructure gaps, and technological scalability. Addressing these challenges requires coordinated efforts across governments, private sector, multilateral organizations, and research institutions to drive down costs, scale up production capacities, and establish robust regulatory frameworks. By investing in innovation and skill development, incentivizing private sector participation, and fostering international collaboration, Africa can accelerate a smooth transition to a sustainable hydrogen economy, unlocking its full potential to decarbonize its economies and create sustainable growth pathways.